2010
DOI: 10.1016/j.neuropsychologia.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Mental state attribution and the temporoparietal junction: An fMRI study comparing belief, emotion, and perception

Abstract: By age 2, children attribute referential mental states such as perceptions and emotions to themselves and others, yet it is not until age 4 that they attribute representational mental states such as beliefs. This raises an interesting question: Is attribution of beliefs different from attribution of perceptions and emotions in terms of its neural substrate? To address this question with a high degree of anatomic specificity, we partitioned the TPJ, a broad area often found to be recruited in theory of mind tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 46 publications
(81 reference statements)
3
26
0
Order By: Relevance
“…An early study revealed that bilateral IPL was more activated by beliefs, but equally activated by fixation (Zaitchik et al, 2010). This finding raises the possibility that belief attribution is possibly similar to the resting state, when the brain is not engaged in any directed task.…”
Section: Depressive Non-self-serving Attribution In Negative Eventsmentioning
confidence: 97%
“…An early study revealed that bilateral IPL was more activated by beliefs, but equally activated by fixation (Zaitchik et al, 2010). This finding raises the possibility that belief attribution is possibly similar to the resting state, when the brain is not engaged in any directed task.…”
Section: Depressive Non-self-serving Attribution In Negative Eventsmentioning
confidence: 97%
“…'she thinks that the door is open' = belief perception vs. 'she is afraid that the door is open' = emotion perception) followed by yes/no has suggested a double dissociation in which EP recruits the right superior temporal gyrus, but belief perception recruits dorsolateral PFC (BA 9) and the middle temporal gyrus (Zaitchik, et al, 2010). Executive control from dorsolateral PFC may be needed because simulating someone's likely state of mind entails holding this representation in mind (working memory), updating it with what is known about reality but suppressing the information about reality that does not apply in the alternative state (inhibition), and the cognitive flexibility to switch between representations (Van Hoeck, et al, 2014).…”
Section: Neuroimaging Data On the Relationship Between Emotion Percepmentioning
confidence: 99%
“…Similarly, the TPJ areas were linked to the representation of mental and non-mental perspectives (Perner et al, 2006; Perner and Leekam, 2008). The right TPJ was specifically linked to the representation of beliefs, as it was found to respond more strongly when reading statements about a person's thoughts than when reading statements about physical appearance or bodily sensations (Saxe and Powell, 2006), and also compared to reading statements about a person's emotions and perceptions (Zaitchik et al, 2010). In another study, an interesting observation was made for the left TPJ.…”
Section: Introductionmentioning
confidence: 99%